COVID-19 pandemic: Experience in Calabar and Implication on the Economic Status of the People - Julius A. Ada; Pius U. Angioha; Egbe E. Tangban; Thelma A. Abang; Pius A. Akam (ARRUS Journal of Social Sciences and Humanities, 2021)
The COVID-19 caused by the SARS-CoV-2, which originated from the Wuhan Province of China during the last days of 2019, has become a global health issue unprecedented since the Spanish influenza of 1918. As of December 30th, there were 86,576 recorded cases of Covid-19 and 1278 confirmed deaths in Nigeria. While the impact of the pandemic varies across societies, for most countries, available evidence reveals that it has increased poverty and inequalities. This study assessed the effect of the Covid-19 pandemic on the economic status of people in Calabar. The survey research method was used in collecting data from a sample of 400 from Calabar, Cross River State, Nigeria. The instrument of data collection was a self-developed unstructured questionnaire. Data were collected within eight days with the aid of five (5) research assistants. Out of the 400-instrument distributed, only 386 was returned and was used for the analysis. Data collected were coded and analyzed using descriptive statistics such as frequency distribution, tables and figures. The result from the descriptive statistics was then subjected to parametric statistics at the 0.05 confidence level. The result from the analysis revealed a significant impact of the covid-19 pandemic on the economic status of people in Calabar, Cross River, Nigeria. Based on the findings, the study recommends, among others, that the government at every level prioritize the distribution of stimulus packages equitably